THE EFFECTIVENESS OF TWO STAY- TWO STRAY TECHNIQUE IN IMPROVING STUDENTS’ READING ABILITY OF NEWS ITEM TEXT (ELang | An English Language Education Journal, 2019)
The research paper is entitled “The Effectiveness of Two Stay- Two Stray Technique in Improving Students’ Reading Ability of News Item Text”. It is written as a particular to fulfilment of the requirements for talking Sarjana Pendidikan degree. This pre-experimental research is done in the fisrt grade of PUQ Pameungpeuk Senior High School. This research is conductedto answer the question Is two stay–two stray technique effective to improve students’ reading ability of news item text to the first grade of Senior High School? What are the students’ response toward the use of two stay- two stray technique in improving students’ reading ability of news item text? The population of this research is the first grade students of PUQ Pameungpeuk Senior High School 2019/2020. They are four classes (10 MIPA 1, 10 MIPA 2, 10 IPS and 10 BAHASA). The number of population is 116 students. The sample is one class in 10 MIPA 1. The number of sample is 30 students as the experimental group. So, the total sample in this research is 30 students. The result of computation shows t-observed is 9.883 and t-table 2.045 (t-observed > t-table, at p= .05). Based on the result above, the researcher conclude that t-observed is higher than t-table. It means that the null hypothesis (Ho) is rejected and the alternative hypothesis is accepted. It meant that two stay – two stay technique was effective for improving students’ reading ability of news item text. Based on the questionnaire, the researcher also got the result that most of the students like two stay- two stray technique in improving students’ reading ability of news item text. Beside that, the students got the motivation and enthusiasm in reading English text by using two stay- two stray technique. It means students of PUQ Pameungpeuk Senior High School gave a positive respond toward the use of two stay- two stray technique. Therefore, the researcher conclude that the first grade students of PUQ Pameungpeuk Senior High School like two stay- two stray technique in improving students’ reading ability of news item text.Key word: Reading, Two Stay- Two Stray